Interaction with Penicillium expansum enhances Botrytis cinerea growth in grape juice medium and prevents patulin accumulation in vitro - Morales-Valle, H. (2013)
Interactions between fungi occur when they grow on the same host plant. This is the case of Botrytis cinerea and Penicillium expansum on grape. P. expansum is also responsible for production of the mycotoxin patulin. In this study, the influence of the interaction between both fungi on fungal growth parameters was studied as well as the effect on the accumulation of patulin by P. expansum. For that purpose, spores of B. cinerea and P. expansum were inoculated together (mixed inoculum), and the parameters growth rate, time for growth and patulin accumulation were assessed. The presence of P. expansum conidia shortened the time for growth of mixed inoculum colonies which, at the end of incubation, were B. cinerea-like. Although some P. expansum growth was observed in mixed inoculum colonies, very low levels of patulin were observed. In assays carried out in patulin-spiked medium, B. cinerea was capable to metabolize the mycotoxin. The capabilities of B. cinerea to shorten time for growth and prevent patulin accumulation are competing abilities that facilitate grape colonization. Significance and Impact of the Study: To our knowledge, this is the first study on the influence of fungal interactions between Botrytis cinerea and Penicillium expansum on growth parameters and patulin accumulation. The incidence of P. expansum in some wine regions is high, but the attack of this fungus to vineyards is rare, being B. cinerea the most common disease. In this assay, it was observed that, in vitro, the presence of P. expansum spores enhanced B. cinerea growth, while the latter avoided patulin accumulation.